2021
DOI: 10.21037/qims-20-823
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of fetal ultrasound diagnostics in cardiac malformations and association with polyhydramnios and oligohydramnios

Abstract: Background: Examine the effectiveness of prenatal ultrasound diagnostics in the detection of cardiovascular malformations, and their association with polyhydramnios and oligohydramnios.Methods: We examined the fetal ultrasonography and postnatal clinical/fetopathological data of 372 newborns/fetuses over a 7-year period in a tertiary centre. Fetal echocardiography was performed in cases of suspected US findings between 18-32 weeks. During the ultrasound the amniotic fluid amount was measured and the amniotic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A study from Hungry found a significant association between CHD and Polyhydramnios. 19 The maximum proportion of CHD, i.e., 50%, was found in the women having an indication of cardiac anomaly on ultrasonography screening, and the correlation between cardiac anomaly on USG and the CHD detection was statistically significant (p value < 0.001). Our findings were similar to those of Nair et al, 8 with a CHD detection rate of 58%, Regmi et al, 9 with a CHD detection rate of 50%, and Li et al, 20 with a CHD detection rate of 64%.…”
Section: Discussionmentioning
confidence: 83%
“…A study from Hungry found a significant association between CHD and Polyhydramnios. 19 The maximum proportion of CHD, i.e., 50%, was found in the women having an indication of cardiac anomaly on ultrasonography screening, and the correlation between cardiac anomaly on USG and the CHD detection was statistically significant (p value < 0.001). Our findings were similar to those of Nair et al, 8 with a CHD detection rate of 58%, Regmi et al, 9 with a CHD detection rate of 50%, and Li et al, 20 with a CHD detection rate of 64%.…”
Section: Discussionmentioning
confidence: 83%
“…A study from Hungry found a significant association between CHD and Polyhydramnios. 19 The maximum proportion of CHD, i.e., 50%, was found in the women having an indication of cardiac anomaly on ultrasonography screening, and the correlation between cardiac anomaly on USG and the CHD detection was statistically significant (p value < 0.001). Our findings were similar to those of Nair et al, 8 with a CHD detection rate of 58%, Regmi et al, 9 with a CHD detection rate of 50%, and Li et al, 20 with a CHD detection rate of 64%.…”
Section: Discussionmentioning
confidence: 83%
“…Because polyhydramnios is highly correlated with fetal AVSD, echocardiograms should be performed when polyhydramnios is detected by ultrasound in any mother who has CHD risk factors, such as viral infection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%